Western lifestyle linked to maladaptive trained immunity - Merbecks, Aurelia Josephine; Mennicken, Christabel; de Graaf, Dennis Marinus; Shkarina, Kateryna; Wagner, Theresa; Latz, Eicke (eLife, 2026)
Trained immunity (TI) refers to a state of innate immune cells that, after encountering an initial stimulus and undergoing epigenetic reprogramming and metabolic changes, allows them to respond more effectively to a subsequent challenge. TI yields a survival advantage, particularly in a pathogen-rich context. However, maladaptive TI may damage the host by exacerbating inflammatory diseases. Here we review which aspects of Western lifestyle may contribute to maladaptive TI, including a Western diet, periodontitis, chronic psychological stress, and environmental triggers such as air pollution and microplastics. Finally, we consider lifestyle intervention as a way to prevent or reduce the impact of maladaptive TI.
Keywords: trained immunity; maladaptive; autoinflammation; infectious disease; Western diet; interleukin-1